Improved CFRTP/AZ31B alloy hybrid joint by surface micro-texture and laser rotational welding technique - Chenghu Jing; Liyuan Sheng; Jihao Xu; Zifa Xu; Di Wu; Junke Jiao (Materials & Design)
As famous lightweight materials, carbon fiber reinforced thermoplastic (CFRTP) composites and magnesium (Mg) alloys are extensively used in the aerospace industry. However, effectively joining CFRTP and Mg alloys while minimizing damage to the CFRTP structure is a critical challenge. In the present research, the micro-textured surface and rotating laser beam welding were applied to successfully join CFRTP and AZ31B Mg alloy. Numerical simulations and experimental validation demonstrated that the sandwich-structured model can accurately predict temperature fields, revealing notable delays and dissipation in heat transfer. Based on the critical laser welding parameters identified through the simulation, the rotating laser beam welding process achieved a relatively uniform remelted zone on the AZ31B alloy, improving thermal transfer to the interface while minimizing the impact on the material. With optimized laser welding parameters, the micro-textured surface of AZ31B alloy effectively formed an interlocking interface for the CFRTP/AZ31B joint by filling microvoids with remelted polyamide. The combined effect of rotating laser beam welding allowed the CFRTP/AZ31B joint to achieve a maximum shear strength of 20.6 MPa.These results suggest a feasible approach for enhancing the adhesion strength of lap joints between CFRTP and AZ31B alloys, offering significant potential for applications in the aerospace industry.